Strengthening Religious Moderation through the Merdeka Student Exchange Program (PMM) at Padang State University - Putra, Rido; Ahmad Rivauzi; Nafsan Nafsan; Indil Setiawan; Lailatul Chomariah (Indonesian Journal of Islamic Religious Education, 2024)
One of the strategic steps to realize religious moderation is through the Merdeka Student Exchange program abbreviated as PMM. The purpose of this research is to analyze and describe how the process of strengthening religious moderation through the PMM program at Padang State University. Religious moderation based on the PMM program is a point of emphasis and an aspect of novelty that has not been revealed in previous research. This research is a field research using qualitative methods. The results found that strengthening religious moderation in PMM students was carried out in three stages: First, the Module Lecturer compiles the logical framework of the Nusantara Module as a reference in carrying out 16 module activities consisting of 8 diversity activities, 2 inspiration activities, 5 reflection activities, and 1 social contribution activity. Second, to strengthen PMM students' understanding of religious moderation, the PMM UNP implementation team organized various activities including learning to get along with the limau baronggeh customary tradition, visiting minority communities in Padang, learning local wisdom with religious and traditional leaders of Kubu Gadang Village. Third, the contribution of Padang State University in strengthening the religious moderation of PMM students is in the form of inserting moderation values in each activity, providing maximum service to all religious believers, and facilitating various activities that support the strengthening of religious moderation.